MALÁRIA SÍMIA NA MATA ATLÂNTICA DO ESPÍRITO SANTO: DISTRIBUIÇÃO E CARACTERIZAÇÃO MOLECULAR DAS ESPÉCIES DE PLASMODIUM A PARTIR DE FEZES DE PRIMATAS - Fagundes Júnior, Jomar (2021)
Malaria is one of the most important infectious diseases in the world. In Brazil, the disease has followed the changes that the country has undergone over the decades. Currently, cases concentrate in the Amazon region, with a small number of them remain in the extra-Amazon region, especially in the areas covered by the Atlantic Forest, where there is a higher number of cases. Questions about the persistence of the disease in the extra-Amazonian region are old, including the possibility of the disease being maintained by animal reservoirs, considering that non-human primates (PNH) can carry parasites typical of human beings and vice versa. These questions regarding the disease gained strength when the importance of Plasmodium knowlesi became evident in maintaining a zoonotic form of malaria in Malaysia, becoming a relevant public health problem. This work aimed to identify the species of parasites that cause simian malaria in the Atlantic Forest region of Espírito Santo State. The investigation consisted of a non-invasive collection of feces from non-human primates in Santa Teresa, Santa Maria de Jetibá, Santa Leopoldina, Domingos Martins, Marechal Floriano, and Laranja da Terra municipalities, in the state of Espírito Santo. It was possible to identify the species of infecting Plasmodium and confirm that they were from non-human primates through DNA extraction and molecular methodologies performed in 29 pools. The extraction for the identification of Plasmodium species was performed using the QIAamp® DNA Mini Stool Kit (Qiagen®). Amplification was performed using real-time PCR (qPCR) to identify Plasmodium species, and conventional PCR was used for simian species identification. The laboratory work took place at the Institute of Tropical Medicine of the University of São Paulo (IMT-USP). The team from the protozoology laboratory of the Institute contributed to the analysis of the fecal sample groups of non-human primates, three pools being found positives (10.34%). Among the positive settings, two had Plasmodium falciparum and one Plasmodium malariae. Two of the samples were collected in Santa Teresa and one in Laranja da Terra. The primate species carrying Plasmodium were identified as Sapajus nigritus and Alouatta guariba, previously described in the literature as carriers of infection by Plasmodium. These animals seem to be important in maintaining the parasite cycle, thus keeping the infection in the region close to the Atlantic Forest. Considering the relationship between human and simian infection observed in Brazil, this information can better define if the disease is behaving as a zoonosis, what would determine targeted public health actions.